Implementasi Building Information Modeling (BIM) 5D Pada Proyek Konstruksi (Studi Kasus Pada Proyek Pembangunan Resto Manggar) - Jaya, Liem Ruwady Pratama; Hendriyani, Irna; Pratiwi, Reno (Universitas Ibn Khaldun, 2025)
With the increasing development of the AEC (Architecture, Engineering and Construction) industry in the current era, there is a lot of software being developed for the needs of the construction industry which aims to minimize human error due to conventional data processing. This research aims to analyze the results of volume and cost comparisons using the 5D Building Information Modeling (BIM) concept with the consultant method on the Resto Manggar Balikpapan Timur construction project. By using Revit, the 2D image obtained from the consultant is modeled again in 3D form where the volume requirements for structural work become more detailed. We can see from the consultant's calculation that the weight is 11,0881.42 kg from the Autodesk Revit software, it is 10,382.58 kg and has a difference of 698.84 kg or 6 %, for the concrete volume results from the consultant of 132.30 m3, the Autodesk Revit software has a volume of 127.01 m3 and has a difference of 5.29 m3 or 4%. To calculate costs for structural work from the consultant, it is IDR. 193,025,200.89 from Autodesk Revit software has a cost of Rp. 181,502,892.27 which has a cost difference of Rp. 11,522,308.62 or 6%, for the calculation of concrete costs by the consultant of Rp. 203,773,342.67 from Autodesk Revit software amounting to Rp. 195,402,397.86 and has a difference in concrete costs of Rp. 8,370,944.81 or 4%. By using the 3D BIM concept supported by Revit software which is able to provide detailed material takeoff results thereby reducing wasted material and supporting the 5D BIM concept to support cost estimation calculations.